Diagnostic excision of the cervix in women over 40 years with human papilloma virus persistency and normal cytology. (July 2019) - Aarnio, Riina; Wikström, Ingrid; Gustavsson, Inger; Gyllensten, Ulf; Olovsson, Matts
Abstract: Objective: Persistent infection with human papillomavirus (HPV) is recognized as the main risk factor of cervical cancer. Investigation via cytology and colposcopy have lower sensitivity than HPV testing in the diagnosis of high-grade cervical intraepithelial neoplasia (CIN2+). Despite normal cytology and colposcopy findings women with persistent HPV infection have an increased risk of CIN2+. The aim of the study was to evaluate the proportion of histologically confirmed CIN2+ in women with persistent HPV infection and normal Pap smears. Study design: From April 2013 until March 2016 we prospectively recruited 91 women over 40 years with persistent HPV infection without any abnormalities in cytology. Of these, 40 women attended a gynecological examination including an HPV test, Pap smear, endocervical cytology, colposcopy with biopsies and diagnostic loop electrosurgical excision procedure (LEEP). Biopsy and LEEP samples were subjected to histological examination Results: CIN2+ was verified by histological examination of the LEEP sample in 6/40 (15%) of the women. All the cytological samples were normal and none of the biopsies confirmed CIN2+. Only 19/40 women still had a persistent HPV infection at the study visit. None of the 21/40 women who had cleared their HPV infection at the study visit had CIN2+ in histology of the LEEP sample. Conclusions: A persistent HPV infection needs to be monitored despite normal Pap smears, since 6/40 (15%) women older than 40 years, was revealed to have an undiagnosed CIN2+ when LEEP was performed. Counseling women regarding the risk of cervical cancer and the expected effect of an eventual LEEP can help them to make an optimal informed choice.